Peran Networking dalam Membangun Karier Sebagai Entrepreneur - Rupina Rupina; Analisa Analisa; Yosia Belo (Student Scientific Creativity Journal, 2025)
Networking plays a crucial role in developing an entrepreneur's career. With a wide network, entrepreneurs can access various resources, business opportunities, guidance and support from investors that can accelerate the development of their business. In addition, networking contributes to building a professional image and trust, which are important factors for attracting customers and strategic partners. Solid interpersonal relationships also open up opportunities for creative collaboration and idea sharing, allowing entrepreneurs to face challenges more effectively. Whether through online or offline platforms, networking is a key strategic element in creating long-term success for an entrepreneur. In the current digital era, networking can be done through various platforms, either directly, such as attending conferences and business events, or online through social media and virtual communities. This process not only expands connections but can also provide an opportunity to understand industry trends and build competitive advantages. Therefore, networking is not just about building relationships, but is also one of the main strategies that can encourage long-term success and growth for an entrepreneur.